Direct reduction of iron ore pellets by H2 and CO: In-situ investigation of the structural transformation and reduction progression caused by atmosphere and temperature. (April 2022) - Scharm, Christoph; Küster, Felix; Laabs, Marcel; Huang, Qiuliang; Volkova, Olena; Reinmöller, Markus; Guhl, Stefan; Meyer, Bernd
Highlights: Hitecom reactor with optical ports for in-situ optical analysis of single iron ore pellets in H2 and CO was established. SEM porosimetry is suitable for identifying single particle effects and is comparable to standard analytical porosimetry. Increasing reduction progress and structural change with rising temperature depending on the reducing atmosphere. Higher reduction swelling index of the pellets under H2 atmosphere. Abstract: With the aim of reducing CO2 emissions in basic industries, the sector of iron and steel metallurgy is also faced with the question of how carbon can be replaced in ore reduction. By means of in-situ observation, this study investigates the direct reduction (DR) of individual iron ore pellets under an atmosphere of hydrogen (H2 ) and carbon monoxide (CO) and at temperatures between 800 °C and 1100 °C at atmospheric pressure. The progress of the reduction, i.e. the phase change and the structural change, is analysed by X-ray diffraction (XRD) and scanning electron microscopy equipped with energy-dispersive X-rays (SEM-EDX). To evaluate the porosities of the pellets, analytical porosimetry is compared to optical porosimetry findings obtained by analysing images of sections in the SEM (hereinafter called SEM porosimetry). Furthermore, the swelling behaviour is evaluated by video analysis and the reduction swelling index (RSI) is determined. The results show a higher reduction progress and a higher RSI under H2 atmosphere than under CO atmosphere. Higher temperatures lead to faster reduction progress and to significant changes in the structural composition of the reduced pellets.